Application Of Reconnecting Methods To Improve Indonesian Learning Outcomes For Class Ii Studentssd Negeri 0511 Batang Tanggal Jae T.P 2020/2021 - Mupida Rohimah Daulay (STKIP Rokania Pasir Pangaraian, 2021)
This research is motivated by the low learning outcomes of students in Indonesian subjects. The formulation of the problem in this study is how the application of the reconnecting method can improve the learning outcomes of Indonesian language subjects for Class II students of SD Negeri 0511 Batang Date Jae. As the subjects in this study, there were 24 students of class II SD Negeri 0511 Batang Date Jae. While the object of this research is to improve student learning outcomes through the reconnecting method. The place of this research is at SD Negeri 0511 Batang Date Jae, especially in class II. The successful application of the reconnecting method on Indonesian language subjects from before the action (pre-action), cycle I, and cycle II. Before the action, student learning outcomes only reached an average percentage of 41.67%, after the action in the first cycle increased to 70.83%, while the second cycle increased to 87.50%. This means that the success of students has reached the success indicators that have been set, which is above 75%. Thus, it can be concluded that through the reconnecting method, it can improve the learning outcomes of Indonesian Class II students SD Negeri 0511 Batang Tanggal Jae